The Influence Of Brand Quality, Store Environment, Perceived Value, On Purchase Decision Of Donuts & Coffee Restaurant Consumers In Jakarta - Nihla Samia; Mutiara Fatihah; Willy Arafah (Universitas Pahlawan Tuanku Tambusai, 2023)
The purpose of this research was to check out the impact of brand quality, store environment, perceived value on purchasing decisions at Donuts restaurant consumers. This analysis methodology uses quantitative primary data, the test phase did is validity and reliability tests100 respondents completed a questionnaire that was used to collect the study's valid data. The sampling method was non-probability sampling with purposive sampling technique. The checking tools used are SPSS version 25 and AMOS Structural Equation Modeling. The results shows that brand quality has no significant positive effect on purchase decision. The results also show that the store environment has no significant positive effect on purchase decision. The findings also reveal that perceived value has significant positive impact on purchase decision. The findings contribute to a recognizing of the importance of influencing factors on Donuts & Coffee consumer purchasing decisions.